Zonal and Zoogeographic Characteristic of the Ant Fauna (Hymenoptera, Formicidae) of Ukraine - Radchenko, A.G. (Вестник зоологии, 2011)
One hundred fourty ant species belonging to 38 genera of 5 subfamilies are known to occur in Ukraine nowadays. All the species are attributed to 16 zoogeographic complexes that are grouped into three faunogenetic classes. Comparative zonal and zoogeographical analysis of the fauna of different geographical regions of Ukraine has revealed their essential heterogeneity. The ant fauna of the Forest-Steppe zone is not original. At the same time, it is not transitive between the faunae of the Forest and Steppe zones. Ant fauna of the Forest-Steppe is related to those not the Steppe but the Forests zones, and the Forest-Steppe can be included in the southern subzone of a Forest zone of t Europe.